Mathematics
         
语言:中文    Language:English
On line Solution of Monovariate Equation:
    Input any unary equation directly, and then click the "Next" button to obtain the solution of the equation.
    It supports equations that contain mathematical functions.
    Current location:Equations > Monovariate Equation > The history of univariate equation calculation > Answer

    Overview: 1 questions will be solved this time.Among them
           ☆1 equations

[ 1/1 Equation]
    Work: Find the solution of equation 2[1-1/3(x-(1+x)/3)] = 1/2(2x-(10-3x)/3) .
    Question type: Equation
    Solution:Original question:
     2(11 ÷ 3 × ( x (1 + x ) ÷ 3)) = 1 ÷ 2 × (2 x (103 x ) ÷ 3)
    Remove the bracket on the left of the equation:
     Left side of the equation = 2 × 12 × 1 ÷ 3 × ( x (1 + x ) ÷ 3)
                                             = 2
2
3
( x (1 + x ) ÷ 3)
                                             = 2
2
3
x +
2
3
(1 + x ) ÷ 3
                                             = 2
2
3
x +
2
9
(1 + x )
                                             = 2
2
3
x +
2
9
× 1 +
2
9
x
                                             = 2
2
3
x +
2
9
+
2
9
x
                                             =
20
9
4
9
x
    The equation is transformed into :
     
20
9
4
9
x = 1 ÷ 2 × (2 x (103 x ) ÷ 3)
     Right side of the equation =
1
2
(2 x (103 x ) ÷ 3)
    The equation is transformed into :
     
20
9
4
9
x =
1
2
(2 x (103 x ) ÷ 3)
    Remove the bracket on the right of the equation:
     Right side of the equation =
1
2
× 2 x
1
2
(103 x ) ÷ 3
                                               = 1 x
1
6
(103 x )
                                               = 1 x
1
6
× 10 +
1
6
× 3 x
                                               = 1 x
5
3
+
1
2
x
                                               =
3
2
x
5
3
    The equation is transformed into :
     
20
9
4
9
x =
3
2
x
5
3

    Transposition :
      -
4
9
x
3
2
x = -
5
3
20
9

    Combine the items on the left of the equation:
      -
35
18
x = -
5
3
20
9

    Combine the items on the right of the equation:
      -
35
18
x = -
35
9

    By shifting the terms and changing the symbols on toth sides of the equation, we obtain :
     
35
9
=
35
18
x

    If the left side of the equation is equal to the right side, then the right side must also be equal to the left side, that is :
     
35
18
x =
35
9

    The coefficient of the unknown number is reduced to 1 :
      x =
35
9
÷
35
18
        =
35
9
×
18
35
        = 1 × 2

    We obtained :
      x = 2
    This is the solution of the equation.



Your problem has not been solved here? Please go to the Hot Problems section!





  New addition:Lenders ToolBox module(Specific location:Math OP > Lenders ToolBox ),welcome。